Mobile Authentication using Hybrid Modalities (MAHM) in Pervasive Computing (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Cloud computing facilities using mobile phones has become a necessity more than being an alternative. Cloud storage, social networks and email communications using mobile phones allows for mobility and on the go access to these cloud services. Despite providing such conveniences to the users, cloud access via mobile devices is vulnerable to security breaches especially when a third party gets hold of the  mobile phone. A third party may have access to the applications and features of the mobile phone provided that the unauthorized user managed to break the security login of the phone. This gives avenue for the unauthorized user to gain access to the cloud services without further verification. Because most of the cloud services provide a single sign-on features whereby the password is used by cloud services (gmail for example) for the first time only. After the first authentication, an authentication token which is downloaded to the mobile phone is used for subsequent authentications. Although this may sound secure without the use of password, the possibility for an unauthorized user access to the cloud services is still possible because the authentication token is stored in the phone itself and does not require further validations. Moreover, the authentication token is stored as plaintext inside the mobile phone and may be susceptible to security breach. Therefore, an identity management system based on user behavior patterns can be used to further validate the authorized user of the cloud services. The main aim of the research is to design MAHM, for cloud service identity management using human behavior patterns classification. There are various biometrics-based authentication using physiological and psychological have been in place but, environmental and human factors can influence these. In this research, unique behavior patterns will be used to identify distinct characteristics of certain individual. The framework will consist of various user behavior such as keypad tapping behavior, keystroke dynamics and phone swiping behavior as authentication scheme to the cloud applications